MOLECULAR DETECTION OF UREC, HPMA, RSBA AND MRPA GENES OF PROTEUS MIRABILIS URINARY TRACT INFECTION IN PATIENT WITH RHEUMATOID ARTHRITIS - & AL-Hashimy, AL-Hamdani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to detect of four important virulence genes (UreC, HpmA, rsbA and mrpA) from Proteus mirabilis bacteria isolated and do the important four blood test (ACPA, RF, ESR, CRP) for patient with urinary tract infection and rheumatoid arthritis in Baghdad/Iraq. Fifty (50) clinical urine samples were collected and cultured on blood agar and macckongy agar. Ten of the samples were identified as P.mirabilis and the automated system VITEK 2 used to complete the identification. Molecular methods using PCR technique targeting UreC, HpmA, rsbA and mrpA genes, using PCR technique and the results were UreC found in 90% of the samples, HpmA 90%, rsbA 100% and mrpA 80%. The P. mirabilis samples were also characterized for antibiotic resistance and the result showed that the majority of samples were show high resistant to Cefotaxime 90%, while the highest susceptibility was against Impenem antibiotic 70%.